Theoretical calculations of excited states and fluorescence spectroscopy using density functional theory - Briggs, Edward A. (2016)
Absorption and emission spectra from the lowest energy transition in BODIPY have been simulated in the gas and water phase using a quantum mechanics/molecular mechanics approach, with DFT and the maximum overlap method (MOM). A post-SCF spin-purification to MOM yields transition energies in agreement with experimental data. Spectral bands were simulated using structures from ab initio molecular dynamics simulations, in which the solvent water molecules are treated classically and DFT is used for BODIPY. The resulting spectra are consistent with experimental data, and demonstrate how absorption and emission spectra in solution can be simulated using a quantum mechanical treatment of the solute. The electronic structure and photoinduced electron transfer (PET) processes in a fluorescent K+ sensor have been studied using DFT and TDDFT to rationalise its function. Absorption and emission energies of the fluorophore-localised intense excitation are more accurately described using MOM than TDDFT. Analysis of molecular orbital energies from DFT calculations in different phases cannot account for the sensors function. It is necessary to consider the relative energies of the electronic states. The inclusion of implicit solvent lowers the energy of the charge transfer state making a reductive PET possible in the absence of K+, while no such process is possible when the sensor is bound to K+. Binding within the ethene–argon and formaldehyde–methane complexes in ground and electronically excited states is studied with equations of motion coupled-cluster theory (EOM-CCSD), MP2 theory and dispersion-corrected DFT (DFT-D). MP2/MOM potential energy curves are in good agreement with EOM-CCSD calculations for the Rydberg and valence states studied. B3LYP-D3 calculations are in agreement with EOM-CCSD for ground and valence excited states, however for Rydberg states significant deviation is observed for a variety of DFT-D methods. Varying D2 dispersion parameters results in closer agreement with EOM-CCSD for Rydberg states.